Influence of chicken meat grinding process conditions on its structural and mechanical characteristics - Stukalska (Ivanova), Nataliia; Kuzmin, Oleg; Dudarev, Igor (My University, 2022)
The greatest degree of destruction of the structure is observed in minced leg meat when using all types of grates. This is explained by the structure of the fabric and its chemical composition. An increase in moisture by 1.60 % and a decrease in fat by 1.74 % and protein by 0.95 % leads to the fact that under the influence of tension in pieces of minced meat, regardless of size, there is a faster loss of asthma-related moisture. Moisture under the influence of tension heats up and partially melts the fat droplets in the minced meat, which is due to faster protein denaturation and an increase in the deformation state of the minced meat.
Keywords: кафедра технології ресторанної і аюрведичної продукції; chicken meat; meat products; raw materials